2019
DOI: 10.1002/bab.1790
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of ZNF 703 in breast cancer tissue: An opportunity for RNAi–NSAID combinatorial therapy

Abstract: Nonsteroidal anti‐inflammatory drugs (NSAIDs) are known to exhibit antitumor activities. Among the very well‐known oncogenes in breast cancer is zinc finger protein 703 (ZNF703) and cyclooxygenase‐2 (COX‐2). Numerous reports indicate a direct link among apoptosis resistance, chemotherapy resistance, and increased expression of ZNF703. In the present study, the expression level of ZNF703 was compared in human breast cancer tissue, healthy breast tissue, and MCF‐7 breast cancer cell line by a real‐time PCR. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Recently, Mishra et al revealed that methylation of ZNF genes could serve as a molecular clustering basis for pancreatic cancer ( Mishra and Guda, 2017 ). A few analyses have focused on the clinical significance of ZNF genes’ expression on drug resistance ( Lee et al, 2013 ; Marzbany et al, 2019 ). Several functional studies on the role of mediating chemoresistance point out that ZNF genes may induce chemoresistance via DNA repair and activation of resistance genes’ transcription ( Rink et al, 2013 ; Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mishra et al revealed that methylation of ZNF genes could serve as a molecular clustering basis for pancreatic cancer ( Mishra and Guda, 2017 ). A few analyses have focused on the clinical significance of ZNF genes’ expression on drug resistance ( Lee et al, 2013 ; Marzbany et al, 2019 ). Several functional studies on the role of mediating chemoresistance point out that ZNF genes may induce chemoresistance via DNA repair and activation of resistance genes’ transcription ( Rink et al, 2013 ; Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Marzbany et al disclosed that there was an increased expression of ZNF703 in breast cancer tissues and cells. 26 Then, we conducted dual luciferase reporter assay to prove the prediction, and Western blot assay implicated that the level of ZNF703 was negatively regulated by miR-491-5p. Furthermore, ZNF703 rescued the activities of miR-491-5p overexpression on proliferation, apoptosis, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…25 Besides, Marzbany et al revealed that the silencing of ZNF703 obviously induced apoptosis of breast cancer cells combined with ibuprofen, which provided a combinatorial therapy for breast cancer. 26 Despite so many researches of ZNF703 in breast cancer, the interaction among H19, miR-491-5p and ZNF703 has not been illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the difference between these cell lines in their mechanism of anticancer resistance. Some cancer origins induce significant activation of inflammatory signals such as NFkB pathway and others have high expression of antiapoptotic proteins that may require other strategies for combination therapies to enhance cancer cell sensitivity [41‐44].…”
Section: Discussionmentioning
confidence: 99%